Tracing the Dinamics of Trade balance in D-8: The Role of Exchange rate and FDI - Suci Wulan Sari; Miftahus Surur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the effect of Foreign Direct Investment (FDI) and exchange rates on the trade balance in the D-8 member countries (Bangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan, and Turkey) during the period 2000 to 2023. The method used is panel data regression with the Fixed Effect Model (FEM), Random Effect Model (REM), and Common Effect Model (CEM) approaches. The selection of the best model is done through the Chow, Hausman, and Lagrange Multiplier (LM) tests. The results show that the exchange rate has a significant effect on the trade balance in all models, indicating that exchange rate fluctuations are an important factor in determining the external trade balance. In contrast, FDI does not show a significant effect, so it has not made a real contribution to improving the trade balance of D-8 countries. Based on the results of the model selection test, the Random Effect model is declared the most appropriate for use in this study. However, all models show positive autocorrelation problems in the residuals, indicating the need for further approaches such as robust estimation to improve the reliability of the results. For the long-term effect, only the Exchange Rate has a significant effect on the Trade Balance, while all variables have no short-term effect. These findings provide policy implications that exchange rate stability and FDI direction are key to strengthening the trade balance of D-8 countries amidst global economic dynamics.